Supporting Patients Treated for Prostate Cancer: A Video Vignette Study With an Email-Based Educational Program in General Practice - Jiwa, Moyez; Halkett, Georgia; Meng, Xingqiong; Pillai, Vinita; Berg, Melissa; Shaw, Tim (JMIR Publications, 2014)
BackgroundMen who have been treated for prostate cancer in Australia can consult their general practitioner (GP) for advice about symptoms or side effects at any time following treatment. However, there is no evidence that such men are consistently advised by GPs and patients experience substantial unmet need for reassurance and advice. ObjectiveThe intent of the study was to evaluate a brief, email-based educational program for GPs to manage standardized patients presenting with symptoms or side effects months or years after prostate cancer treatment. MethodsGPs viewed six pairs of video vignettes of actor-patients depicting men who had been treated for prostate cancer. The actor-patients presented problems that were attributable to the treatment of cancer. In Phase 1, GPs indicated their diagnosis and stated if they would prescribe, refer, or order tests based on that diagnosis. These responses were compared to the management decisions for those vignettes as recommended by a team of experts in prostate cancer. After Phase 1, all the GPs were invited to participate in an email-based education program (Spaced Education) focused on prostate cancer. Participants received feedback and could compare their progress and their performance with other participants in the study. In Phase 2, all GPs, regardless of whether they had completed the program, were invited to view another set of six video vignettes with men presenting similar problems to Phase 1. They again offered a diagnosis and stated if they would prescribe, refer, or order tests based on that diagnosis. ResultsIn total, 64 general practitioners participated in the project, 57 GPs participated in Phase 1, and 45 in Phase 2. The Phase 1 education program was completed by 38 of the 57 (59%) participants. There were no significant differences in demographics between those who completed the program and those who did not. Factors determining whether management of cases was consistent with expert opinion were number of sessions worked per week (OR 0.78, 95% CI 0.67-0.90), site of clinical practice (remote practice, OR 2.25, 95% CI 1.01-5.03), number of patients seen per week (150 patients or more per week, OR 10.66, 95% CI 3.40-33.48), and type of case viewed. Completion of the Spaced Education did impact whether patient management was consistent with expert opinion (not completed, OR 0.88, 95% CI 0.5-1.56). ConclusionsThe management of standardized patients by GPs was particularly unlikely to be consistent with expert opinion in the management of impotence and bony metastasis. There was no evidence from this standardized patient study that Spaced Education had an impact on the management of patients in this context. However, the program was not completed by all participants. Practitioners with a greater clinical load were more likely to manage cases as per expert opinion.